ANTIBODY TITER AGAINST SPERMATOZOAL ANTIGENS OF BULLS IN BLOOD SERA OF COWS AND HEIFERS WITH DIFFERENT NUMBER OF INSEMINATION - Aleksandar Milovanović; Miodrag Lazarević; Danijela Kirovski; Milovan Jovičin; Tomislav Barna (Archives of Veterinary Medicine, 2008)
In this paper are presented the results obtained by determining antibody titar of IgA and IgG class against spermatozoal antigens and extenders for bull’s semen using the method of indirect immunofluorescence in blood sera of cows and heifers. Spermatozoids, prepared for artificial insemination, were suspended in TRIS egg yolk and herbal „Biociphos+” extender. Animals were divided in four groups according to the number of total inseminations in their life: virgin heifers; cows and heifers inseminated 1-5 times; 6-10 times inseminated cows and cows inseminated more than 10 times. The obtained results clearly point that there is a system humoral response of the immune system towards spermatozoids and/or semen extender. Titers of total antisperm antibodies increase with the number of inseminations. This increase is a consequence of increased titer of antisperm antibodies of the IgA class. Obviously, antibodies against spermatozoids of the IgG class have no important influence.